2020
DOI: 10.1088/1361-648x/ab9d4c
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between stacked structures and weak itinerant magnetic properties of La2xYxNi7compounds

Abstract: Hexagonal La2Ni7 and rhombohedral Y2Ni7 are weak itinerant antiferromagnet (wAFM) and ferromagnet (wFM), respectively. To follow the evolution between these two compounds, the crystal structure and magnetic properties of A2B7 intermetallic compounds (A = La, Y, B = Ni) have been investigated combining X-ray powder diffraction and magnetic measurements. In the present study, the La2-xYxNi7 intermetallic compounds with 0 ≤ x ≤ 1 crystallize in the hexagonal structure (Ce2Ni7-type) with Y preferentially located i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
3
2
1
Order By: Relevance
“…Although the synthesis process slightly differs depending on the composition. Figure 7 shows that for the A2Ni7 binary compounds (A = Y, Gd, Sm or La), the ratio of hexagonal/rhombohedral structure increases with rA, same effect has been reported in the (NdA)1.5Mg0.5Ni7 (A=La,Y) system [26] as welle as (La,Y)2Ni7 system [26,27]. As for the pseudo-binary compounds, the content of hexagonal phase increases with xLa.…”
Section: Structural Properties Of the Pseudo-binary Systems A2-xlaxni7supporting
confidence: 67%
See 1 more Smart Citation
“…Although the synthesis process slightly differs depending on the composition. Figure 7 shows that for the A2Ni7 binary compounds (A = Y, Gd, Sm or La), the ratio of hexagonal/rhombohedral structure increases with rA, same effect has been reported in the (NdA)1.5Mg0.5Ni7 (A=La,Y) system [26] as welle as (La,Y)2Ni7 system [26,27]. As for the pseudo-binary compounds, the content of hexagonal phase increases with xLa.…”
Section: Structural Properties Of the Pseudo-binary Systems A2-xlaxni7supporting
confidence: 67%
“…This can be understood based on a geometric effect: La is larger than Y, Sm or Gd, thus it fills the 4f2 H (6c1 R ) sites with higher coordination number than the 4f1 H (6c2 R ) ones (20 versus 16). This result has been confirmed by DFT calculation for the system La2-xYxNi7, where it was shown that the enthalpies of formation are lower with Y occupying the [A2Ni4] subunit sites and La the [ANi5] subunit one [27]. Replacing Y by La in the [ANi5] slabs leads to an expansion of this slab parallel to the ab plan [15,29].…”
Section: Structural Properties Of the Pseudo-binary Systems A2-xlaxni7mentioning
confidence: 53%
“…Liu et al [34] and Zhao et al [35] studied the effects of yttrium substitution in A 2 B 7type phases of La-Y-Ni-Mn-Al and found that Y induced the formation of the H-A 2 B 7 compositions. These observations however contradict other studies indicating that the yttrium presence favoured the R-A 2 B 7 phase formation [36,37]. Zhao et al [35] also reported that the studied La 1 -x Y x Ni 3.25 Mn 0.15 Al 0.10 (x = 0.00-1.00) intermetallic compounds had a single hydrogen ab/desorption plateau, while Liu [34] reported on the formation of two hydrogen ab/desorption plateaus for a similar sample series, La 3 -x Y x Ni 9.7 Mn 0.5 Al 0.3 (x = 1, 1.5, 1.75, 2, 2.25, 2.5), which is in line with observations reported for other A 2 B 7 -type materials [12,37,38].…”
Section: Introductioncontrasting
confidence: 99%
“…This suggests that while initially, Y occupy the A 2 B 4 subunits, once filled up (x ≥ 1), it prefers entering the AB 5 subunits. Such behaviour has been previously reported and was related to a lower coordination number of 16 at the 4f 1 site when compared with coordination number 20 at the 4f 2 site [36]. The higher Y concentration in the samples also shortens the 4f 1 -4f 1 distance in the neighbouring unit cells from 3.282(3) to 3.170 (7) Å for Y 0.33 and Y 1.67 , respectively.…”
Section: Hr Sr-pxd and Pndsupporting
confidence: 79%
“…Unlike La 2 Ni 7 , Latroche et al [22] found that the hydrogen storage capacity of Y 2 Ni 7 alloy did not decay after several hydrogen absorption/desorption cycles at 0.1 and 0.7 MPa, and the alloy structure remained unchanged, but there were three hydrogen absorption/desorption plateaus at 10 MPa and the plateau pressures were higher (0.055 MPa, 0.5 MPa, 2.9 MPa); therefore, Y 2 Ni 7 alloy was not properly used as an alloy electrode material. Paul-Boncour et al [23] studied the La 2−x Y x Ni 7 (x = 0-2) alloy and found that Y preferentially occupies La sites in the [A 2 B 4 ] subunit and the atomic radius of Y (R Y = 2.27 Å) is smaller than that of La (R La = 2.74 Å); the addition of Y in La-Y-Ni alloys helps to adjust the volume mismatch between the [A 2 B 4 ] and [AB 5 ] subunits. Therefore, the effect of Y in La-Y-Ni alloys is similar to the Mg in La-Mg-Ni alloys.…”
Section: Introductionmentioning
confidence: 99%